2022
DOI: 10.1021/acs.nanolett.1c03698
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Enhancement in Single Organic Radical Molecules

Abstract: Organic thermoelectric materials have potential for wearable heating, cooling, and energy generation devices at room temperature. For this to be technologically viable, high-conductance (G) and high-Seebeck-coefficient (S) materials are needed. For most semiconductors, the increase in S is accompanied by a decrease in G. Here, using a combined experimental and theoretical investigation, we demonstrate that a simultaneous enhancement of S and G can be achieved in single organic radical molecules, thanks to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 32 publications
0
51
0
Order By: Relevance
“…Apart from the electron transport, a few of the recent reports have also witnessed the spintronic applications of QI effects. An anomalous effect of QI in organic-radical based spin filters with the reversal of para-meta conductance was realized in our previous work which is recently certified by an experimental observation . Pal et al demonstrated the spin-polarized currents in a silver–vanadocene–silver single molecule junction stemming from the spin-dependent QI features .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the electron transport, a few of the recent reports have also witnessed the spintronic applications of QI effects. An anomalous effect of QI in organic-radical based spin filters with the reversal of para-meta conductance was realized in our previous work which is recently certified by an experimental observation . Pal et al demonstrated the spin-polarized currents in a silver–vanadocene–silver single molecule junction stemming from the spin-dependent QI features .…”
Section: Introductionmentioning
confidence: 99%
“…An anomalous effect of QI in organic-radical based spin filters with the reversal of para-meta conductance was realized in our previous work 46 which is recently certified by an experimental observation. 47 vanadocene−silver single molecule junction stemming from the spin-dependent QI features. 48 53 Gehring et al experimentally demonstrated the QI effects in electronic transmission in graphene nanoconstrictions.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results revealed p-type conduction, 1.2 eV energy gap between the Fermi level and HOMO of BDT, and a positive linear relation between the Seebeck coefficient and the length of single molecules [426]. Recently, a combination of experimental and theoretical work revealed that the Seebeck coefficient and electrical conductance of single organic radical molecules can be simultaneously enhanced due to their intrinsic spin state [427]. 1,2,4-benzotriazin-4-yl (Blatter) radical molecules with pseudo-meta (meta) and pseudo-para (para) connections to two gold electrodes and the closed-shell (non-radical) quinazoline analogue have been designed to test this idea.…”
Section: Single Moleculesmentioning
confidence: 88%
“…[11,12] Despite the rich promise of radical-based molecular electronics, attempts to date to incorporate persistent organic radicals into single-molecule junctions at room temperature have resulted in loss of the open-shell character, [13] or in a modest enhancement of electrical conductance. [8,14] The significant increase in charge transport efficiency predicted by theoretical studies [6] has only been observed at cryogenic temperatures. [15,16] These observations are not entirely surprising, as the open-shell molecular components used in previous studies had either a highly delocalised radical state (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…a resonance) at the Fermi level results in high charge transport efficiency. The high slope of T(E) vs E near the Fermi energy offered by radical systems is also predicted to give rise to enhanced Seebeck coefficients, [8] leading to enticing prospects for the design of molecular thermoelectric materials, [6,9,10] whilst the presence of an unpaired electron provides the basis from which to extend electronics to spintronics. [11,12] Despite the rich promise of radical-based molecular electronics, attempts to date to incorporate persistent organic radicals into single-molecule junctions at room temperature have resulted in loss of the open-shell character, [13] or in a modest enhancement of electrical conductance.…”
Section: Introductionmentioning
confidence: 99%